Morphological selection of teak (Tectona grandis) clones resistant to mistletoe infestation - ZAINAL MUTTAQIN; FEBI NURILMALA NUH; ISKANDAR ZULKARNAIN SIREGAR; ARIS WIBOWO; SRI RAHAYU (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Muttaqin Z, Nuh FN, Siregar IZ, Wibowo A, Rahayu S. 2025. Morphological selection of teak (Tectona grandis) clones resistant to mistletoe infestation. Biodiversitas 26: 4851-4864. Until now, study about the teak clones of Jati Plus Perhutani (JPP) resistance to mistletoe, which is very rarely of it in both Indonesia and other regions. The purpose of this study focuses on selecting teak clones with resistance to mistletoe by analyzing their morphological characters. In the study location at East Java, Indonesia, both the Clonal Seed Orchard (CSO) plot in Padangan, the JPP plot and the Seed Production Stand (SPS) plot in KPH Ngawi, the sample plot design follows the modified EFForTS/CRC990 guidelines. By contrast, the JPP plot utilizes the "tree pair method," where one stripe plot is free of mistletoe, whereas a paired stripe contains mistletoe. The parameters observed in related to the morphology of teak clones include 52 characters. Data analysis used the MVSP software, and Principal Component Analysis (PCA) to determine the significance of each morphological character based on the Eigenvalue and the percentage of variance of PCA. The phenogram results for CSO Padangan revealed five clusters have mixed both mistletoe-free and mistletoe-affected trees. The JPP plot exhibited two clusters with one cluster clearly consisted of teak trees without mistletoe. The SPS plot also displayed two clusters of only one cluster distinctly contained teak trees without mistletoe relatively. The key resistant teak clones identified were four morphological descriptors found mainly in the JPP plot showed a positive correlation: total height, number of branches, the leaf vein corners, the leaf base shape, the base of stem groove. Conversely, six characters exhibited a negative correlation: branch free height, petiole length, bark thickness, inner stem color, upper surface of the leaf, leaf flesh. Furthermore, it will be needed to test similarity some morphological descriptors significantly from the result of this study compare with of them of plants of tissue culture that taken of shoots superior teak clone.